Dextroamphetamine Modulates the Response of the Human Amygdala - Hariri, Ahmad R; Mattay, Venkata S; Tessitore, Alessandro; Fera, Francesco; Smith, William G; Weinberger, Daniel R (Neuropsychopharmacology (New York, N.Y.), 2002)
Amphetamine, a potent monoaminergic agonist, has pronounced effects on emotional behavior in humans, including the generation of fear and anxiety. Recent animal studies have demonstrated the importance of monoamines, especially dopamine, in modulating the response of the amygdala, a key brain region involved in the perception of fearful and threatening stimuli, and the generation of appropriate physiological and behavioral responses. We have explored the possibility that the anxiogenic effect of amphetamine in humans reflects the drug's influence on the activity of the amygdala. In a double-blind placebo controlled study, fMRI revealed that dextroamphetamine potentiated the response of the amygdala during the perceptual processing of angry and fearful facial expressions. Our results provide the first evidence of a specific neural substrate for the anxiogenic effects of amphetamine and are consistent with animal models of dopaminergic activation of the amygdala.